IMPACT OF CULTURAL DIVERSITY ON TEACHING ENGLISH IN PUBLIC PRIMARY SCHOOLS IN UZBEKISTAN - Muminova, Sohiba Nurboboyevna (Educational Research in Universal Sciences, 2023)
Three Uzbek teachers having at least one-year experience educating English to Russian children in public primary schools in Uzbekistan were selected as participants. The teachers were chosen based on their previous experience teaching English in a culturally diverse classroom. Wu (2016) says choosing participants with experience teaching English to children from diverse cultural backgrounds is critical for reliability and validity.